Cross-Listing, Investment Sensitivity to Stock Price, and the Learning Hypothesis - Foucault, Thierry; Frésard, Laurent (Review of Financial Studies, 2012)
[Cross-listed firms in the United States have a higher investment-to-price sensitivity than do firms that never cross-list. This difference is strong, does not exist prior to the cross-listing date, and does not vanish afterward. Moreover, it does not appear to be primarily driven by improvements in governance, disclosure, and access to capital associated with a U.S. crosslisting. Instead, we argue that a cross-listing enhances managers' reliance on stock prices because it makes stock prices more informative to them. Consistent with this explanation, U. S. cross-listings that are more likely to strengthen the informativeness of stock prices for managers feature a higher investment-to-price sensitivity.]